2009
DOI: 10.1007/s10344-009-0252-9
|View full text |Cite
|
Sign up to set email alerts
|

Ranging behaviour and socio-biology of Eurasian otters (Lutra lutra) on lowland mesotrophic river systems

Abstract: We examined the spatial structure and sociobiology of a native wild population of Eurasian otters (Lutra lutra) on mesotrophic rivers in a mild temperate climate. Radio-tracking of 20 individuals revealed exclusive intra-sexual adult home-ranges. Adult female homeranges (7.5 km, SD=1.5 km, n=7) were inversely related to river width (R 2 adj ¼ 0:68, F 6 = 13.5, P=0.014) and so appeared to be based on food resources. The aquatic area within adult male home-ranges (30.2 ha, SD=9.5 ha, n=5) was greater than that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A reintroduced otter population in the north‐east Iberian Peninsula followed a similarly rapid expansion, with 23 liberated animals occupying more than 300 km of rivers and streams only 2 years after being released (Saavedra, 2002). Rapid spread of otters in newly colonized areas and areas of reintroduction can be related to the availability of high‐quality habitats but also to the release from intra‐specific interactions, which play a major role in the use of space by otters (see Ó Néill et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…A reintroduced otter population in the north‐east Iberian Peninsula followed a similarly rapid expansion, with 23 liberated animals occupying more than 300 km of rivers and streams only 2 years after being released (Saavedra, 2002). Rapid spread of otters in newly colonized areas and areas of reintroduction can be related to the availability of high‐quality habitats but also to the release from intra‐specific interactions, which play a major role in the use of space by otters (see Ó Néill et al. , 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Eurasian otter are considered to have the widest distribution of all 13 otter species (Yoxon & Yoxon, 2019), with large home ranges, broad trophic niche breadth, and the ability to exploit multiple food resources, including those of terrestrial origin. For instance, a 3-month Irish telemetry study observed a mean home range of 7.5 AE 1.5 km (mean AE SD) for females occupying mesotrophic rivers and a home range of 13.2 AE 5.3 km for males occupying rivers of various productivity (mesotrophic and oligotrophic) (Ó Néill et al, 2009). Therefore, it is highly likely that spraints collected in a given area may not contain microplastics or even prey collected and ingested from that area, with some coastal spraints (e.g., Achill Island and Killary fjord) also possibly containing marine species, which could not be determined following the microplastic isolation process.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the only fish likely to be able to eat an Atlantic salmon smolt and move that far inland are sea trout ( Salmo trutta ). It is also important to note that otters’ home ranges tend to remain below 20 km (Erlinge, 1967; Néill, Veldhuizen, de Jongh, & Rochford, 2009) and, as such, it is unlikely that the three tags which moved more than 20 km upstream were ingested by otters. Ultimately, further research would be required to be able to individually identify the predator(s) responsible for these upstream movements.…”
Section: Discussionmentioning
confidence: 99%